Judicial Independence: will we always have Luxembourg? - Cervell Hortal, María José (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Judicial independence has become a recurrent issue in the case law of the Court of Justice of the European Union in recent years. Threats to the rule of law, notably in Poland, have generated intense judicial activity. This article discusses how the cases connected with the Polish crisis (but also with other states), have contributed to outlining a concept of judicial independence in the European Union and how the Court has become the best guarantor of its respect in the Member States.
Keywords: judicial Independence; rule of law; EU values